On The Static Reliability Of Binary-State And Multi-State K-Out-Of-N:G Systems - Shaker, Shawki; Sabah, Safa (Iraqi Journal of Science, 2023)
The k-out-of-n:G (or k/n:G) system structure is a very popular of redundancy infault-tolerant systems, with wide applications in so many fields. This paper presentstwo states of multi-state k/n:G systems. The first part, we present the definition thatintroduced by Al-Neweihi et al [1], where the values are the same with respectto all system states and we show that there exists an alternative equivalent definitionto Al-Neweihi’s definition. In the second part of this paper we give more generaldefinition proposed by Huang et al [2], where it allows different values withrespect to different system states and we provide there exists an equivalent definitionto Huang’s definition when the values are increasing. We show it is simply togeneralize the mathematical theory of static reliability of binary k/n:G systems to themultistate k/n:G systems. Several new results are established concerning theevaluation of the stochastic of the system static performance measures, together withtheir computer algorithm (Belfour algorithm).